Penguatan Visi Pendidikan Bangsa Melalui Implementasi Pendidikan Akhlak dalam Kitab Syi'ir Ngudi Susilo di Pondok Pesantren Baiturrahman Beran Ngawi - Yulianto Nur Cahyono; Yanti (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
Moral education is an essential component in shaping the character of individuals and society. Islam encourages the practice of good moral values as a moral foundation in everyday life. Pondok Pesantren Baiturrahman Beran in Ngawi has chosen the Kitab Syi’ir Ngudi Susilo as a tool to teach noble morals to its students. The Kitab Syi’ir Ngudi Susilo contains lessons on noble morals and virtues, written in Pegon script, making it easier for readers to memorize its verses and apply them in their daily activities. This research aims to delve into the implementation of moral education in the Kitab Syi’ir Ngudi Susilo at Pondok Pesantren Baiturrahman Beran and how this contributes to strengthening the national education vision. To achieve the objectives of this research, the author collected primary data through observations and interviews with the head and council of teachers (asatidz) at Pondok Pesantren Baiturrahman Beran in Ngawi, who have a deep understanding and direct involvement with the students. The results of this research show that the teachers/asatidz always emphasize that the students at the Islamic boarding school should have good morals, no matter where or when they are. The students are taught to show respect to their parents before leaving for the school, wear neat attire, and pay attention to the teachers/asatidz during the teaching process. When the lessons begin, the students should be well-prepared with their writing tools, books, and the Kitab to be studied by the teachers/asatidz.